Studies on Biology of Hadda Beetle, Epilachna vigintioctopunctata: A Serious Pest of Wild Beeter Gourd, Momordica dioica - Deshmukh, Pradeep S. (Recent Research Advances in Biology Vol. 8, 2021)
Beetles play a significant role in the economy for two reasons. Plant feeders are pests of farm crops and forest trees when they are numerous. Predatory species, on the other hand, contribute significantly to man's attempt to control plant feeder pests. Pests are animals whose populations grow to such an extent that they cause economic losses to crops or are a nuisance and health hazard to humans and their livestock. Momordica dioica Roxb (wild bitter gourd) fruits are less bitter than Momordica charantia L. fruits (bitter gourd).It also has medicinal properties. It is a wild annual plant with a low ability to germinate. It has a lower production than bitter guard but a higher market value. On the wild bitter gourd Momordica dioica, Epilachna larvae (grubs) and adults were spotted attacking. However, current research shows that it is a pest of cucurbitaceous hosts as well as Momordica dioica. It causes defoliation and stunted development, resulting in a lower yield.